Do radioiodine-avid lymph nodes from differentiated thyroid cancer on the initial posttherapy scan need repeated 131I therapy? - Jiang, Yongji; Liu, Simin; Qiu, Xiaotong; Huo, Yanlei; Zhang, Xiaoying; Cai, Haidong; Lv, Zhongwei; Ma, Chao (Frontiers in Endocrinology, 2023)
Background: Residual/recurrent lymph node metastase (LNM) is often found after differentiated thyroid cancer (DTC) surgery. This study aimed to investigate whether patients complicated with radioiodine-avid (131I+) lymph nodes from DTC on the initial posttherapy scan (PTS) need repeated 131I therapy. Methods: From June 2013 to August 2022, DTC patients with 131I+ lymph nodes on the initial PTS who received at least two cycles of 131I therapy were retrospectively enrolled. They were divided into a complete response (CR) group and an incomplete response (IR) group according to their response to the initial 131I therapy based on the 2015 American Thyroid Association (ATA) guidelines. Results: A total of 170 DTC patients with 131I+ lymph nodes on the initial PTS were included; 42/170 (24.7%) patients were classified into the CR group and 128/170 (75.9%) were classified into the IR group according to their response to the initial 131I therapy. None of the 42 CR patients had disease progression at the subsequent follow-up, and 37/170 (21.8%) IR patients improved after repeated therapy. Univariate analysis showed that N stage (P=0.002), stimulated thyroglobulin (sTg) level before initial 131I therapy (P<0.001), LNM size (P<0.001), number of total residual/recurrent LNM (P=0.021), radioiodine-nonavid (131I-) LNM (P=0.002) and ultrasound features (P<0.001) were related to the initial treatment response. On multivariate analysis, sTg level (OR=1.186, P<0.001) and LNM size (OR=1.533, P=0.004) were independent risk factors for IR after initial 131I therapy. The optimal sTg level and LNM size cutoff value for predicting the treatment response after initial 131I therapy were 18.2 µg/l and 5mm. Conclusions: This study suggested that approximately one-quarter of patients with 131I+ lymph nodes on initial PTS, especially those with N0 or N1a stage, lower sTg level, smaller LNM size, ≤2 residual/recurrent LNMs, negative ultrasound features and no 131I- LNM, remain stable after one cycle of 131I therapy and do not need repeated therapy.